The Transgender Identity Survey: A Measure of Internalized Transphobia - Bockting, Walter O. (LGBT Health, 2020)
Purpose: We describe the development of a measure of internalized transphobia, defined as discomfort with one's transgender identity as a result of internalizing society's normative gender expectations. Methods: An item pool was created based on responses from a small clinical sample (N = 12) to an open-ended questionnaire. Expert judges reviewed the items, resulting in a 60-item instrument for empirical testing. We conducted exploratory factor analysis (EFA) by using a community sample of 430 transgender individuals (aged 18–72, mean [M] = 37.4, standard deviation [SD] = 12.0), and confirmatory factor analysis (CFA) by using an online sample of 903 transgender individuals (aged 18–66, M = 31.6, SD = 11.1). Construct validity was examined by using correlations with instruments assessing related constructs administered to the online sample. Results: EFA resulted in a 52-item instrument with four subscales: Pride, Passing, Alienation, and Shame. CFA, after removal of half of the items, retained the four-factor structure. The final 26-item scale showed excellent internal consistency (0.90) and test–retest reliability (0.93). The factors showed a pattern of association with crossgender identity, gender ideology, outness, felt stigma, self-esteem, and psychological distress consistent with moderate-to-good construct validity. Conclusion: Internalized transphobia can be conceptualized as four inter-related dimensions: pride in transgender identity (reverse scored), investment in passing as a cisgender person, alienation from other transgender people, and shame. The Transgender Identity Survey reliably assesses this construct, useful in research to understand the impact of minority stress on transgender people's health. It can also be used in clinical practice to assess internalized transphobia at intake and follow-up.